1999
DOI: 10.1021/jo9908593
|View full text |Cite
|
Sign up to set email alerts
|

Carboindation of Carbon−Carbon Triple Bonds:  Regioselective Indium-Mediated Allylation of Functionalized Alkynes and Transformation into Halogen-Substituted 1,4-Dienes

Abstract: By examining the allylindation of a series of substituted alkynes, the relationships between allylindation reactivity and alkyne structure were systematically investigated. While terminal alkynes with protected hydroxyl groups gave the corresponding allylated branched 1,4-dienes (Markovnikov products) within 5-6 h, the unprotected alkynols reacted markedly faster, requiring only 2-4 h of ultrasonication in THF to produce the 1,4-dienols in good yields. In the latter reactions, the regioisomeric outcome was fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(22 citation statements)
references
References 31 publications
0
21
0
1
Order By: Relevance
“…7a,b They carried out the reaction of allylindium reagents and unactivated alkynes in THF to obtain various 1,4-pentadienes in good-to-high yields. The Markovnikov product (vide infra) was obtained selectively and the involvement of a vinylic a,a-bis-indium intermediate A more systematic study on the carboindation of carbone carbon triple bonds was carried out by Klaps and Schmid in 1999, as shown in Scheme 4. 8 They found that unprotected alkynols reacted with allylindium reagents markedly faster, requiring only 2e4 h of ultrasonication in THF to produce the products in good yields.…”
Section: Carbonecarbon Triple Bondsmentioning
confidence: 99%
See 2 more Smart Citations
“…7a,b They carried out the reaction of allylindium reagents and unactivated alkynes in THF to obtain various 1,4-pentadienes in good-to-high yields. The Markovnikov product (vide infra) was obtained selectively and the involvement of a vinylic a,a-bis-indium intermediate A more systematic study on the carboindation of carbone carbon triple bonds was carried out by Klaps and Schmid in 1999, as shown in Scheme 4. 8 They found that unprotected alkynols reacted with allylindium reagents markedly faster, requiring only 2e4 h of ultrasonication in THF to produce the products in good yields.…”
Section: Carbonecarbon Triple Bondsmentioning
confidence: 99%
“…The Markovnikov product (vide infra) was obtained selectively and the involvement of a vinylic a,a-bis-indium intermediate A more systematic study on the carboindation of carbone carbon triple bonds was carried out by Klaps and Schmid in 1999, as shown in Scheme 4. 8 They found that unprotected alkynols reacted with allylindium reagents markedly faster, requiring only 2e4 h of ultrasonication in THF to produce the products in good yields. In this reaction, the regioisomeric outcome was found to depend on the distance between the hydroxyl group and the alkyne moiety; propargyl alcohol gave the anti-Markovnikov product via the involvement of a bicyclic chelation-controlled transition state 5, while 4-pentynol and higher homologs exclusively afforded the branched 1,4-dienes, the Markovnikov products.…”
Section: Carbonecarbon Triple Bondsmentioning
confidence: 99%
See 1 more Smart Citation
“…B. der formalen Synthese von (À)-Mycalamid A (190) (Schema 17). [148] In [158][159][160][161] eine Lewis-säurekatalysierte Addition von Allylsilanen oder Allylstannanen [162][163][164] oder auch eine Palladium-katalysierte Addition von Allylhalogeniden an Alkine. [165] 5.3.…”
Section: Intermolekulare Alken-alkin-kupplung Zu 14-dienenunclassified
“…[7] More recently, it was reported that allylation of unactivated terminal alkynes by treatment with allylindiums provided branched 1,4-dienes through regioselective Markovnikov addition.…”
Section: Introductionmentioning
confidence: 99%